Boron Carbides as Efficient, Metal‐Free, Visible‐Light‐Responsive Photocatalysts1. Issue 11 (28th January 2013) - Liu, Jikai; Wen, Shuhao; Hou, Yang; Zuo, Fan; Beran, Gregory J. O.; Feng, Pingyun
<x xml:space="preserve">Abstract</x> From armor plating to photocatalysis: Two photocatalysts based on boron carbides, B4.3C and B13C2, are reported. The more stable and efficient B4.3C exhibits H2 evolution rates of about two orders of magnitude higher than graphitic C3N4, and without the need for noble metal cocatalysts. Also, both materials can act as photocathodes for photoelectrochemical water reduction under visible light irradiation.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>